Elucidating the Role of Stress Granule Dynamics in the Pathogenesis of ALS - Manser, Charlotte (Université d'Ottawa / University of Ottawa, 2026)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by the selective degeneration of the upper and lower motor neurons (MNs). Currently, there is no cure and treatment options are limited, resulting in poor prognosis. Over 50 genes have been implicated in ALS, 35 of which are directly linked to familial forms of the disease. These genes span diverse biological functions, yet converge on similar pathology and clinical outcomes, highlighting the complexity of ALS pathology. In up to 97% of ALS cases, the RNA binding protein TDP-43 is mislocalized and aggregated, making it a key therapeutic target. TDP-43 inclusions are thought to result, in part, from the dysregulation of stress granules (SGs)- transient cytoplasmic structures that sequester mRNA during cellular stress. While some ALS-associated genes are known to regulate SG biology, many remain uncharacterized. This work investigates the role of ALS-associated genes in SG dynamics using a refined loss-of-function high-throughput microscopy screen, which identifies the neuronal nicotinic acetylcholine receptor (nAChR) subunit β4 as a novel regulator. Mutations in CHRNβ4 are overrepresented in patients with sALS, implicating dysfunctional cholinergic signaling in MN vulnerability. RNA-mediated knockdown of CHRNβ4 altered TDP-43 localization, increased cytosolic calcium during oxidative stress, and promoted SG fusion, leading to the production of fewer but larger SGs. Similarly, perturbation of nAChR activity through CHRNβ4 knockdown or pharmacological targeting altered SG production and morphology, consistent with a role for calcium-dependent signaling in the cellular stress response. Inhibition of PLC and other phosphoinositide pathway effectors, which act downstream of nAChRs and are implicated in calcium-dependent signaling produced comparable SG phenotypes. Collectively these findings identify nAChRs as novel regulators in ALS through mechanisms involving calcium signaling and the stress response. Systematic interrogation of ALS-associated genes that influence calcium-dependent pathways controlling SG dynamics may provide additional insights into disease mechanisms and therapeutic targets for ALS.
Keywords: Amyotrophic lateral sclerosis; Neurodegeneration; CHRNB4; Nicotinic acetylcholine receptors; Stress granules; TDP-43; Calcium signaling; Oxidative stress; Phospholipase C